Formation of the Archetype of Siberian Landscape in Jewelry and Stone-Product Products87 - M. Lobatskaya, R.; A.Berman, E. (International Journal of Engineering and Technology, 2018)
The archetype of the landscape in the jewelery and stone-cutting art of Eastern Siberia in the form of separate elements, according to reliable artifacts, was originated in the late Paleolithic. These landscape compositions appear for the first time in Scythian toreutics, where they mark the transition from the â€œbestialâ€ style to narrative folklore images. In the later jewelry art of the indigenous people of Eastern Siberia, the landscape was not a reflection of the real landscape, but a mythologized dream endowed with a mandatory magical meaning. Modern works of artists of Irkutsk represent a synthesis of philosophical understanding of images of Siberian nature and universal aesthetic values, and their artistic style is dictated by both personal aesthetic preferences of artists or schools, and their chosen material and processing technologies.Â Â